Chlamydia trachomatis Infection Is Associated with E-Cadherin Promoter Methylation, Downregulation of E-Cadherin Expression, and Increased Expression of Fibronectin and α-SMA—Implications for Epithelial-Mesenchymal Transition - Rajić, Jovana; Inic-Kanada, Aleksandra; Stein, Elisabeth; Dinić, Svetlana; Schuerer, Nadine; Uskoković, Aleksandra; Ghasemian, Ehsan; Mihailović, Mirjana; Vidaković, Melita; Grdović, Nevena; Barisani-Asenbauer, Talin (Frontiers in Cellular and Infection Microbiology, 2017)
Chlamydia trachomatis (Ct) can induce scarring disease of the ocular mucosa, known as trachoma, the most common infectious cause of blindness worldwide. We hypothesized that epithelial-mesenchymal transition (EMT) contributes to the fibrotic process in trachomatous scarring. Infection of human conjunctival epithelial cells (HCjE) with Ct activated signaling pathways involved in EMT induction, which was correlated with decreased expression of E-cadherin, guardian of the epithelial phenotype. In addition, Ct infection was associated with increased expression of two mesenchymal cell markers: fibronectin and α-SMA. The DNA methylation statuses of selected regions of E-cadherin, fibronectin, and α-SMA genes revealed that Ct infection was accompanied with changes in DNA methylation of the E-cadherin promoter, while the expression of the two mesenchymal markers was not related with this epigenetic event. Our data suggest that Ct infection of conjunctival epithelial cells induces EMT-like changes that go along with modification of the methylation profile of the E-cadherin promoter and could, as one of the earliest events, contribute to processes triggering conjunctival scarring.